Graduating Students’ Perception on their Experiences of attending a Christian-based Higher Educational Institution - Bourne, Paul Andrew (Journal of Advanced Research in English & Education, 2021)
Many critical factors impact Christian educational practice. A critical challenge facing religious institutions is whether they can critically embrace the post-modernist perspective and its attending culture of post-modernity; whether they can embrace unity-in-diversity, allowing all viewpoints to be accorded value, while at the same time preserving the essential parameters of belief, structure, and practice. This study aims to empirically examine the perception of graduates of the private higher educational institution on the programme and product offerings of the institution, and make pertinent information available for research-based decisions. An objectivist epistemology is employed to evaluate the issues. The 2017 Graduating Student Exit Survey (GSES) comprised 242 graduates (46.5%) of the graduating population. The sample was selected solely based on attendance. On August 11, 2017, all attendees were seated in the university’s auditorium; they were informed of a survey to solicit data on the ‘institution’s product’ including a self-reported evaluation of the programme. The graduates were informed of their rights and freedom to complete such an instrument, and that they could opt not to complete the process. One in every two students was given a copy of the instrument based on the seating arrangement of every second seat. Of the intended sampling size (n=260), 93.1% completed the survey instrument. When the respondents were asked ‘If you had to do it all over again, would you attend the institution?’ a significant statistical correlation existed between the two variables, with more respondents of the SDA faith indicated yes to the question, 82.4% compared to non-faith-based members (64.4%; χ2 (df=2) = 10.100, P =0.006). ‘Would you recommend the institution as a place of study to others? By being a faith-based member of the SDA movement. A significant statistical relationship existed between the two variables, with more respondents of the SDA faith indicated yes to the question. (93.3%) compared to non-faith-based members (χ2(df=2) = 16.201, P < 0.0001). All stakeholders of the institution must begin to value the customer and no longer should it be ‘student’, but the new concept must be ‘customer’, and as such effort should be placed on pleasing the customer as this is the gateway to changing the discontent and dissatisfactions that have been expressed by some of the 2017 graduates. How to cite this article:  Bourne PA. Graduating Students’ Perception on their Experiences of attending a Christian-based Higher Educational Institution. J Adv Res Eng & Edu 2020; 5(1): 20-38.